The Effect of Competence and Compensation on Employee Performance with Job Satisfaction as an Intervening Variable at PLN UP2D Sumut - Hasrizal; Elfitra Desi; Sri Rahayu (CV. Doki Course and Training, 2026)
The purpose of this study was to assess how competency and compensation influence employee performance, with job satisfaction as a mediating factor at PLN UP2D North Sumatra. A quantitative approach using a survey method was used. The study population consisted of all employees at PLN UP2D North Sumatra, with a sample size of 117 employees selected through a saturated sampling technique. Data were collected through questionnaires and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that competency and compensation significantly and positively influenced job satisfaction. Furthermore, competency, compensation, and job satisfaction together had a positive and significant influence on employee performance. In addition, job satisfaction was shown to effectively mediate the relationship between competency and compensation related to employee performance. These results highlight that improving employee competency and establishing a fair compensation framework, along with initiatives to improve job satisfaction, can lead to improved employee performance. This study aims to add knowledge in human resource management theory and serve as a resource for PLN leadership in optimizing employee performance.